Creando Espacios : boletin del Proyecto PAPI. (New York : Proyecto PAPI, 1998)
Fonds Suzan Daniel (FSD)
Periodiciteit : halfjaarlijks?
Redactie : GMHC, 119 W 24th Street, New York, NY 10011
Spaans
Periodiek